Meningkatkan Kompetensi Guru Berbasis Komunitas bagi MGMP SMP Kota Blitar - Miranu Triantoro; Udin Erawanto (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
Teachers as the main factor in implementing learning need to improve their competence, both professional, pedagogic, personal and social competence. By having complete competence, the teacher will have the expected responsibilities based on laws and regulations. One of the teacher competencies that needs to be developed is writing a scientific article competence. Facts in the field show that many of the teachers have "low" competence in compiling a scientific work. Therefore, community service that focuses on writing scientific journal articles is organized by focusing more on practical activities and mentoring. At the end of the meeting there was a mutual agreement from the participants to finish their idea articles within a week.